Cultural differences in scene perception - Alotaibi, Albandari (2016)
Do individuals from different cultures perceive scenes differently? Does culture have an influence on visual attention processes? This thesis investigates not only what these influences are, and how they affect eye movements, but also examines some of the proposed mechanisms that underlie the cultural influence in scene perception. Experiments 1 & 2 showed that Saudi participants directed a higher number of fixations to the background of images, in comparison to the British participants. British participants were also more affected by background changes, an indication of their tendency to bind the focal objects to their contexts. Experiments 3 & 4 revealed a higher overall number of fixations for Saudi participants, along with longer search times. The intra-group comparisons of scanpaths for Saudi participants revealed less similarity than within the British group, demonstrating a greater heterogeneity of search behaviour within the Saudi group. These findings could indicate that the British participants have the advantage of being more able to direct attention towards the goals of the task. The mechanisms that have been proposed for cultural differences in visual attention are due to particular thinking styles that emerge from the prevailing culture: analytic thinking (common in individualistic cultures) promotes attention to detail and a focus on the most important part of a scene, whereas holistic thinking (common in collectivist cultures) promotes attention to the global structure of a scene and the relationship between its parts. Priming methodology was used in Experiments 5, 6 & 7 to cue these factors, although it did not reveal any significant effects on eye movement behaviours or on accuracy at recognition of objects. By testing these explanations directly (Experiment 8), findings have mainly suggested the holistic-analytic dimension is one of the main mechanisms underlying cultural diversity in scene perception. Taken together, these experiments conclude that the allocation of visual attention is also influenced by an individual’s culture.